2017
DOI: 10.1007/s10681-017-1917-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of simple sequence repeat markers for sweetpotato weevil resistance

Abstract: The development of sweetpotato [Ipomoea batatas (L.) Lam] germplasm with resistance to sweetpotato weevil (SPW) requires an understanding of the biochemical and genetic mechanisms of resistance to optimize crop resistance. The African sweetpotato landrace, 'New Kawogo', was reported to be moderately resistant to two species of SPW, Cylas puncticollis and Cylas brunneus. Resistance has been associated with the presence of hydroxycinnamic acids esters (HCAs), but the underlying genetic basis remains unknown. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 37 publications
(46 reference statements)
0
31
0
Order By: Relevance
“…All programs prioritized high β-carotene content, and beginning in 2014, studies in Mozambique included evaluation of Fe and Zn content. The national agricultural research institutes' breeding programs emphasized development and accelerated release of cultivars (Low et al, 2020), with the national breeding program in Uganda developing specific procedures for breeding for weevil resistance (Yada et al, 2017a), the major pest problem in SSA. In addition, all sub-regional and national programs prioritized selection of clones with high dry matter content, with desired minimum levels varying due to taste differences in different countries.…”
Section: Adapting Population and Variety Improvement Schemesmentioning
confidence: 99%
“…All programs prioritized high β-carotene content, and beginning in 2014, studies in Mozambique included evaluation of Fe and Zn content. The national agricultural research institutes' breeding programs emphasized development and accelerated release of cultivars (Low et al, 2020), with the national breeding program in Uganda developing specific procedures for breeding for weevil resistance (Yada et al, 2017a), the major pest problem in SSA. In addition, all sub-regional and national programs prioritized selection of clones with high dry matter content, with desired minimum levels varying due to taste differences in different countries.…”
Section: Adapting Population and Variety Improvement Schemesmentioning
confidence: 99%
“…The high level of genetic diversity observed in the New Kawogo × Beauregard population reported here supports the observation of some progeny exhibiting transgressive segregation for resistance to SPW. Variation in SPW infestation observed in the F 1 population of these two parents was significant and transgressive segregation for SPW resistance was observed in the F 1 sibs ( Yada et al, in press ). The progeny that was more resistant than New Kawogo and others with high HCA esters are new candidates for selection and can be used as sources of genes for future crop improvement ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 96%
“…The objective of this study was to determine the segregation pattern of resistance to SPW in a bi-parental cross between New Kawogo and Beauregard. Association analyses of SPW resistance and SSR markers was recently reported for this same population ( Yada et al, in press ) and a genetic map based on SNP markers is currently being developed for this population under the Genomic Tools for Sweetpotato Improvement (GT4SP) project (Yencho, unpublished) with the overarching aim of facilitating the identification of quantitative trait loci associated with sweetpotato weevil resistance.…”
Section: Introductionmentioning
confidence: 94%
“…Bt proteins and hydroxycinnamic acids both cause mortality in SPW larvae and in combination increased mortality as is expected for an additive effect. We suggest that Bt strains that can be expressed effectively in the root cortex of sweetpotato could enhance resistance mediated by hydroxycinnamic acid esters, and should be explored as a trait that breeders can exploit for biorational pest management of sweetpotato weevils (Otema et al 2017;Yada et al 2017), but future development of multiple component resistance should consider the potential for interactions of different mechanism that reduce efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…SPW control using conventional pesticides is complicated because sweetpotato roots are subterranean, and the target insect spends the majority of its lifecycle inside roots protected by the soil. Hydroxycinnamic acids esters (hexadecyl and octadecyl-cinnamic acid esters, hexadecylcaffeic acid esters and 5-O-caffeoylquinic acid) are produced naturally by the roots and are biologically active against SPW larvae at ecologically relevant concentrations (Stevenson et al 2009) and have been identified as a breeding trait for improved varieties (Otema et al 2017;Yada et al 2017). These compounds are particularly effective at protecting against oviposition by adults because they occur at the highest concentrations at the root surface where eggs are laid and induce behavioural avoidance after feeding and creating feeding holes in which eggs are laid (Anyanga et al 2013) but are less effective against the larval stage which causes the most damage in the cortex.…”
Section: Introductionmentioning
confidence: 99%